2017
DOI: 10.1002/1873-3468.12901
|View full text |Cite
|
Sign up to set email alerts
|

Differential requirement for ATG2A domains for localization to autophagic membranes and lipid droplets

Abstract: ATG2 is one of the autophagy-related (ATG) proteins essential for autophagosome formation and localizes to isolation membranes and lipid droplets in mammalian cells. Here, we investigated the requirement of regions in ATG2A for its organellar localization and function. The N-terminal amino acids 1-198 and the C-terminal amino acids 1830-1938 are required for the localization to isolation membranes and lipid droplets, respectively. The C-terminal region is not required for the localization to isolation membrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
102
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(114 citation statements)
references
References 41 publications
7
102
0
Order By: Relevance
“…Using confocal imaging and flow cytometry to quantify, tandem-tagged LC3B puncta in ATG2A/2B DKO cells under complete medium (CM) or starvation conditions were both GFP-and mCherry-positive ( Fig 3A and quantified in 3B). This indicated that the ATG2A/B DKO U2OS cells had impaired autophagy flux, consistent with previous work [46]. Stable reconstitution of tandem-LC3B expressing ATG2A/B DKO cells with ATG2A-WT resulted in more mCherryonly-positive cells/puncta in CM conditions that were increased upon starvation and was nullified using bafilomycin A1 (to prevent lysosome acidification and quenching of GFP signal) ( Fig 3A and quantified in 3B).…”
supporting
confidence: 90%
See 1 more Smart Citation
“…Using confocal imaging and flow cytometry to quantify, tandem-tagged LC3B puncta in ATG2A/2B DKO cells under complete medium (CM) or starvation conditions were both GFP-and mCherry-positive ( Fig 3A and quantified in 3B). This indicated that the ATG2A/B DKO U2OS cells had impaired autophagy flux, consistent with previous work [46]. Stable reconstitution of tandem-LC3B expressing ATG2A/B DKO cells with ATG2A-WT resulted in more mCherryonly-positive cells/puncta in CM conditions that were increased upon starvation and was nullified using bafilomycin A1 (to prevent lysosome acidification and quenching of GFP signal) ( Fig 3A and quantified in 3B).…”
supporting
confidence: 90%
“…The depletion of TRAPC11 results in a phenotype similar to that of ATG2A/B DKO and ATG2A-mLIR [53]. The mammalian ATG2 proteins, ATG2A and ATG2B, have been shown to be essential for phagophore formation and closure [32,33,46], and depletion of WIPI4, a constitutive interaction partner of mammalian ATG2s, also negatively impacts on phagophore closure [29]. Herein, we have described a hitherto unidentified GABARAP/GABARAP-L1 interaction region on both ATG2A and ATG2B that is essential for phagophore formation.…”
Section: Atg2a-lir Is Essential For Autophagosome Formationmentioning
confidence: 99%
“…Some of the structures in the ATG2‐depleted cells appeared circular in shape. However, because circular structures were not seen in ATG2A/ATG2B double knockout cells, such structures in the depleted cells probably resulted from an incomplete inactivation of the protein. Indeed, only small membranes were seen in the absence of both ATG2 proteins, supporting the notion that ATG2 is required for isolation membrane elongation.…”
Section: Discussionmentioning
confidence: 97%
“…Both binding regions were shown to be important for autophagy . Furthermore, the existence of two membrane‐binding regions in ATG2A was suggested by truncational analysis in vivo . The IM edge and ERES assume a high curvature and PI3P is enriched in the IM .…”
Section: Establishment Of the Membrane‐tethering Activity Of Atg2mentioning
confidence: 99%
“…37 Furthermore, the existence of two membrane-binding regions in ATG2A was suggested by truncational analysis in vivo. 38 The IM edge and ERES assume a high curvature 39 and PI3P is enriched in the IM. 40 Moreover, the N-terminal portion of Atg2 was shown to be sufficient for targeting green fluorescent protein to the ER.…”
Section: Osawa and Nodamentioning
confidence: 99%